Thyroid transcription factor-1 positive primary breast cancer: a case report with review of the literature - Westre Bjørn; Aas Hans; Gundersen Marian D; Chen Ying; Klingen Tor A; Sauer Torill (BMC, 2010)
Abstract This case describes an infiltrating breast tumour with thyroid transcription factor-1 (TTF-1) positive staining and ductal differentiation in a 72-year-old woman. The presence of ductal carcinoma in situ with positive TTF-1 is a strong indication that this is a primary tumour and not a metastasis from lung. On PET scan and CT follow up there were no other tumours found in this patient. We are not aware of any previously reported TTF-1 positive primary breast carcinoma with ductal differentiation.